2012
DOI: 10.1063/1.3685891
|View full text |Cite
|
Sign up to set email alerts
|

Overtone-induced dissociation and isomerization dynamics of the hydroxymethyl radical (CH2OH and CD2OH). I. A theoretical study

Abstract: The dissociation of the hydroxymethyl radical, CH(2)OH, and its isotopolog, CD(2)OH, following the excitation of high OH stretch overtones is studied by quasi-classical molecular dynamics calculations using a global potential energy surface (PES) fitted to ab initio calculations. The PES includes CH(2)OH and CH(3)O minima, dissociation products, and all relevant barriers. Its analysis shows that the transition states for OH bond fission and isomerization are both very close in energy to the excited vibrational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 56 publications
3
52
0
Order By: Relevance
“…This conclusion agrees with the experimental exclusive detection of CH 3 O (Pirim et al 2010). Remarkably, calculated ∆E /L2 values for CH 3 O and CH 2 OH formation (14.5 kJ mol −1 and 41.1 kJ mol −1 ) agree reasonably well with those obtained by Kamarchik et al (2012) at the CCSD(T)/augcc-pvtz (22.6 kJ mol −1 and 47.1 kJ mol −1 ). The ZPE corrections do not affect the general trends described above (see values in brackets of Table 1), the main effects are an increase of the ∆E and ∆E r values by about 4 kJ mol −1 and 30 kJ mol −1 at most.…”
Section: Results Of Quantum Chemical Calculationssupporting
confidence: 80%
See 1 more Smart Citation
“…This conclusion agrees with the experimental exclusive detection of CH 3 O (Pirim et al 2010). Remarkably, calculated ∆E /L2 values for CH 3 O and CH 2 OH formation (14.5 kJ mol −1 and 41.1 kJ mol −1 ) agree reasonably well with those obtained by Kamarchik et al (2012) at the CCSD(T)/augcc-pvtz (22.6 kJ mol −1 and 47.1 kJ mol −1 ). The ZPE corrections do not affect the general trends described above (see values in brackets of Table 1), the main effects are an increase of the ∆E and ∆E r values by about 4 kJ mol −1 and 30 kJ mol −1 at most.…”
Section: Results Of Quantum Chemical Calculationssupporting
confidence: 80%
“…Previous works (Saebo et al 1983;Geers et al 1993;Walch 1993;Dertinger et al 1995;Taketsugu et al 1996;Marcy et al 2001;Petraco et al 2002;Kamarchik et al 2012) examined the isomerization of CH 3 O into CH 2 OH as a way to reach the most stable isomer, but both experiment and theory concluded that this isomerization is unlikely because the barrier for isomerization is significantly higher than the CH 3 O dissociation barrier. Accordingly, and considering the cryogenic temperatures of the interstellar medium at which the processes occur, formation of CH 2 OH is kinetically hampered in favor of CH 3 O formation.…”
Section: Results Of Quantum Chemical Calculationsmentioning
confidence: 99%
“…Therefore the C s symmetry-constrained geometry optimization has been performed by employing the B3LYP/6-311++G(d, p) method. The Gaussian package (Frisch et al 2009) has been used, and the resulting geometry, in close agreement with that of Kamarchik et al (2012), is cast in Table 1.…”
Section: Quantum Chemical Calculationsmentioning
confidence: 90%
“…At equilibrium, CH 2 OH is a non-planar species belonging to the C 1 point group with unequal CH bond lengths. However, it is well accepted (Johnson & Hudgens 1996;Kamarchik et al 2012) that this radical in its ground vibrational state effectively behaves as a planar molecule of C s symmetry with a 2 A electronic ground state. Therefore the C s symmetry-constrained geometry optimization has been performed by employing the B3LYP/6-311++G(d, p) method.…”
Section: Quantum Chemical Calculationsmentioning
confidence: 99%
“…Hydroxymethyl radical, CH 2 OH, has been the subject of over 100 experimental and theoretical papers in the last 40 years, 1 in large measure due to the important role it plays as a reactive intermediate in combustion and environmental chemistry. 2 As one example, the combustion initiation step for oxygenated hydrocarbon fuels such as methanol is thought to be hydrogen abstraction by O 2 to produce hydroxymethyl radical, i.e., CH 3 OH + O 2 → CH 2 OH + HO 2 .…”
Section: Introductionmentioning
confidence: 99%